Investigating communication capabilities of CityGML and IFC for 3D city modelling - Φλώρος, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2017)
“Smart cities” is a relatively new scientific field, applied to an increasing number of application fields. This evolution though, urges data collection and integration, hence major issues arise that need to be tackled. One of the most important challenges is the heterogeneity of collected data, especially if those data derive from different standards and vary in terms of geometry, topology and semantics. Another key challenge is the efficient analysis and visualization of spatial data, which due to the complexity of the physical reality in modern world, 2D GIS struggles to cope with. So, in order to facilitate data analysis and enhance the role of smart cities, the 3rd dimension needs to be implemented. Within this context, standards such as the CityGML and the Industry Foundation Classes (IFC) although fulfill this necessity, they present major differences in their schemas, thus rendering their integration a challenging task. On one hand, CityGML is an open standard that stores and represents information of the entities that can be addressed in a modern 3D city model, while on the other hand IFC describes in maximum detail the construction of a building from an architectural point of view. The aim of this thesis is to investigate the integration possibilities of the aforementioned standards, starting from generating the IFC model and ending with generating a CityGML LoD 4 model, able to preserve its semantic information and be further extended with multiple attributes and properties.